Students' perception of effective English listening strategies, a survey at Dong Hu hight school, Thai Nguyen = Nhận thức của học sinh về chiến lược nghe tiếng Anh hiệu quả. Một nghiên cứu tại trường THPT Đồng Hỷ, Thái Nguyên . M.A Thesis Linguistics: 60 - Dương, Thị Hòa (University of Languages and International Studies, 2017)
65 p. + CD-ROM